Use of Apple Pomace for Intensification of Biogas Production in the Anaerobic Digestion of Cattle Manure - Polishchuk V.; Shvorov S.; Kucheruk P.; Zablodskiy М.; Galchynska Ju.; Zubok T.; Pasichnik N.; Valiev T. (Problems of the Regional Energetics, 2024)
Ukraine Abstract. The goal of the work is to increase the yield of methane in biogas plants due to the joint methane fermentation of cattle manure with apple pomace. To achieve this goal, the following tasks were solved: the yield of biogas from cattle manure was determined with the addition of apple pomace to the substrate and fermentation in psychrophilic and mesophilic temperature conditions of the biogas plant. Based on the obtained experimental data of fermentation at temperatures of 22±1°C and 36±1°C of the fermenter, the biogas yield was assessed and the rational temperature regime for the operation of the biogas plant was determined. The studies were carried out on a laboratory biogas plant, consisting of a fermenter and a wet-type gasholder. A glass container with a total volume of 3 dm3 was used as a fermenter. The novelty of the chosen topic lies in the fact that the maximum methane output rate was determined under periodic loading of the fermenter, which for the psychrophilic temperature regime is 0.0033 m3/(kg DOM∙day), and in the mesophilic temperature regime mode 4 times more - 0.012 m3/(kg DOM∙day). The significance of the results lies in the fact that based on the results of the dynamics of methane output during periodic loading of the fermenter, it is possible to predict a constant methane output in industrial biogas plants that operate in a quasi-continuous mode, which will be equal to the maximum methane output during periodic loading of the fermenter.